Utilization of Telemedicine in Addressing Musculoskeletal Care Gap in Long-Term Care Patients. (April 2020) - Cheng, Olivia; Law, Nok-Hin; Tulk, Jessica; Hunter, Michelle
Abstract : Background: A notable proportion of patient transfers in Ontario are from long-term care facilities for consultation of musculoskeletal (MSK) issues. These transfers are costly for patients and the healthcare system. This study evaluated the utility of a telemedicine MSK (TeleMSK) service for long-term care patients requiring an orthopaedic consultation. Method: A cross-sectional study was used to assess TeleMSK from September 2018 to April 2019. Twenty-six long-term care facilities participated in this study, which included 32 long-term care patients assessed via TeleMSK and 27 telemedicine liaisons. The Telehealth Satisfaction Scale and the Telemedicine Usability Questionnaire (TUQ) surveys were used to evaluate the usefulness of the TeleMSK program. Results: Patients and families rated voice (64.3%) and visual (71.4%) quality of TeleMSK to be excellent as well as the length of consultation (92.9%). A total of 78.6% of participants rated explanations from physicians to be excellent and 92.9% of the participants rated the carefulness, skillfulness, respect, and sensitivity of the attending physician to be excellent 85.7%. Patients felt privacy and confidentiality was maintained and respected throughout the consultation. Most telemedicine liaisons agreed that TeleMSK improved accessibility and productivity of consultations, and 81.5% of the telemedicine liaisons strongly agreed that they would use TeleMSK again in the future. Conclusion: TeleMSK allowed for accessible, timely orthopaedic consultations without compromising the quality of patient care. Patients, families, and telemedicine liaisons rated their experience and the use of TeleMSK as excellent. Barrier to health care is an important issue in the long-term care population. TeleMSK is an excellent medium to close this gap.